2012
DOI: 10.1542/peds.2010-3091
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Zinc as Adjuvant Therapy for Severe Pneumonia in Young Children

Abstract: BACKGROUND AND OBJECTIVE: Diarrhea and pneumonia are the leading causes of illness and death in children <5 years of age. Zinc supplementation is effective for treatment of acute diarrhea and can prevent pneumonia. In this trial, we measured the efficacy of zinc when given to children hospitalized and treated with antibiotics for severe pneumonia. METHODS: We enrolled 610 children aged 2 to 35 months who presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 18 publications
8
74
0
3
Order By: Relevance
“…The primary objective of this RCT was to measure the effect of up to 14 days of daily zinc supplementation on time to recovery from severe pneumonia and treatment failure. These results, and predictors for treatment failure and cessation of severe pneumonia, have been described elsewhere (21,22). The study included children aged 2-35 months with severe pneumonia who were referred to Kanti Children´s hospital Emergency or Outpatient departments.…”
Section: Study Design and Study Populationmentioning
confidence: 92%
See 2 more Smart Citations
“…The primary objective of this RCT was to measure the effect of up to 14 days of daily zinc supplementation on time to recovery from severe pneumonia and treatment failure. These results, and predictors for treatment failure and cessation of severe pneumonia, have been described elsewhere (21,22). The study included children aged 2-35 months with severe pneumonia who were referred to Kanti Children´s hospital Emergency or Outpatient departments.…”
Section: Study Design and Study Populationmentioning
confidence: 92%
“…The children were discharged with advice to the parents to continue amoxicillin and to complete antibiotic treatment of a total of 10 days. Details of both inclusion and exclusion criteria are described previously (21) and are listed in Figure 1.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The supplementation duration was 5-14 d or until discharge from a hospital. For primary outcomes, eight studies (9,10,(12)(13)(14)(15)(16)(17) reported time to recovery from severe pneumonia, with five (9,(12)(13)(14)(15) reporting HR and 95 % CI; five (9,10,(14)(15)(16) reported HLOS, with three (9,14,15) reporting HR and 95 % CI; six (9,12,(14)(15)(16)(17) reported treatment failure; and five (9,12,14,16,17) reported change of antibiotics.…”
Section: Baseline Characteristics and Risk Of Biasmentioning
confidence: 99%
“…Among the thirteen studies, four were excluded, of which one (23) was an advanced abstract of an included study, two (24,25) focused on children with severe acute lower respiratory tract infection (LRTI) but not severe pneumonia and one (26) used the same data from the included trial. Finally, nine RCT (9)(10)(11)(12)(13)(14)(15)(16)(17) were included.Baseline characteristics and risk of bias …”
mentioning
confidence: 99%